Gender Disparities in Anti-dementia Medication Use among Older Adults: Health Equity Considerations and Management of Alzheimer's Disease and Related Dementias - Lu, Z. Kevin; Xiong, Xiaomo; Wang, Xinyuan; Wu, Jun (Frontiers in Pharmacology, 2021)
Objective: The prevalence of Alzheimer’s disease and related dementias (ADRD) in women is higher than men. However, the knowledge of gender disparity in ADRD treatment is limited. Therefore, this study aimed to determine the gender disparities in the receipt of anti-dementia medications among Medicare beneficiaries with ADRD in the U.S. Methods: We used data from the Medicare Current Beneficiary Survey 2016. Anti-dementia medications included cholinesterase inhibitors (ChEIs; including rivastigmine, donepezil, and galantamine) and N-methyl-D-aspartate (NMDA) receptor antagonists (including memantine). Descriptive analysis and multivariate logistic regression models were implemented to determine the possible gender disparities in the receipt of anti-dementia medications. Subgroup analyses were conducted to identify gender disparities among beneficiaries with Alzheimer’s disease (AD) and those with only AD-related dementias. Results: Descriptive analyses showed there were statistically significant differences in age, marital status, and Charlson comorbidities index (CCI) between Medicare beneficiaries who received and who did not receive anti-dementia medications. After controlling for covariates, we found that female Medicare beneficiaries with ADRD were 1.7 times more likely to receive anti-dementia medications compared to their male counterparts (odds ratio [OR]: 1.71; 95% confidence interval [CI]: 1.19–2.45). Specifically, among Medicare beneficiaries with AD, females were 1.2 times more likely to receive anti-dementia medications (Odds Radio: 1.20; 95% confidence interval: 0.58–2.47), and among the Medicare beneficiaries with only AD-related dementias, females were 1.9 times more likely to receive anti-dementia medications (OR: 1.90; 95% CI: 1.23–2.95). Conclusion: Healthcare providers should be aware of gender disparities in receiving anti-dementia medications among patients with ADRD, and the need to plan programs of care to support both women and men. Future approaches to finding barriers of prescribing, receiving and, adhering to anti-dementia medications by gender should include differences in longevity, biology, cognition, social roles, and environment.